MANAJEMEN PEMBIAYAAN PENDIDIKAN DALAM DINAMIKA KEBIJAKAN PENDIDIKAN MENENGAH - Hardanti, Deskania; Mahardhani, Ardhana Januar; Adipura, Lalan Ferary; Rochmawati, Nur Intan; Septiani, Sisca (EDUPEDIA, 2026)
Educational financing management is a strategic element in secondary education policy because it plays a crucial role in determining the effectiveness of achieving quality, equity, and sustainability. This study aims to analyze educational financing management within the dynamics of secondary education policy through a conceptual and policy approach. The study employed a qualitative method based on literature review, analyzing academic books, reputable national and international journal articles, and relevant policy documents. The analysis was conducted using content and thematic analysis techniques to identify patterns, concepts, and the implementation of secondary education financing policies. The study's results indicate that the main problem with secondary education financing lies not only in the size of the budget, but also in the quality of financing management, which encompasses planning, governance, accountability, performance orientation, and the principle of fairness. The study's synthesis formulated a conceptual model that places financing management at the core of secondary education policy, with three main pillars: governance, performance orientation, and distributive justice. The implications of this study emphasize the importance of strengthening integrated, needs-based, and sustainable educational financing management to support improvements in the quality and equity of secondary education.